Writing to exist: Mes'adet Bedirhan's pleas for Ottoman women. - Kadıoğlu, Ayşe (Women's History Review, 2025)
Mes'adet Bedirhan was an eloquent author who wrote for the pioneer Ottoman feminist journal called Kadınlar Dünyası (Women's World) published in Istanbul between 1913 and 1921. She wrote multiple pieces in the Ottoman Turkish and French editions of the journal in 1913–1914. Although very few traces of her life story exist in the historical accounts of the era, she left a mark in this world through her own act of writing. This article not only generates new information about her life but also endeavors to reflect on the overall content of her essays. Through these essays, she showed Ottoman women that they can change their destiny once they discovered their innate strength. She not only underlined women's agency in contesting their unequal position in the society but also criticized her feminist sisters in the west for representing the Ottoman women as silent and submissive objects of pleasure.